KEHIDUPAN PENYEMBAHAN DI ERA PENTAKOSTA KETIGA DAN IMPLIKASINYA TERHADAP AMANAT AGUNG - Twin Hosea Widodo Kristyanto; Dony Lubianto; Soewandi H. Tandiawan; Fredy The (The Way: Jurnal Teologi dan Kependidikan, 2022)
The Third Pentecostal Movement, as a development of Pentecostal theology, has influenced the worship life of Pentecostals. This paper aims to explain how the worship life in the Third Pentecost era and its relation to the completion of the Great Commission of the Lord Jesus. Qualitative methods are used to achieve this goal, using a systematic and phenomenological literature study approach toward 4 interviewees. The results of the observations show that the worship life in the Third Pentecost era is characterized by a special spirituality, namely emphasizing the practice of speaking in tongues and providing space for other manifestations of the power of the Holy Spirit. It is the practice of spirituality that attracts people and ultimately provides momentum for the preaching of the gospel. In addition, the spirituality of the Third Pentecost is also marked by a life of prayer and intense meditation on God's Word as well as the fellowship of believers in cell groups. This spirituality encourages God's people to carry out evangelism and discipleship so that more people experience God. Spirituality in the Third Pentecostal era is not only self-empowerment, but also missionary. Thus, it can be concluded that the worship life in the Third Pentecost era is characterized by an emphasis on the use of tongues (glossolalia), a life of prayer and meditation on the Word, and the practice of discipleship through cell groups as bridges and media for the completion of the Great Commission of the Lord Jesus.